The effect of agricultural extension service on the technical efficiency of Teff (Eragrostistef) producers in Ethiopia - Elias, A.; Nohmi, M.; Yasunobu, K.; Ishida, A.; Alene, A. (Science Publishing Group, 2014)
Teff (Eragrostistef) is a major staple food crop in Ethiopia, but smallholder teff production is characterized by persistently low average yield. A major government effort aimed at raising the productivity and competitiveness of smallholder agriculture in Ethiopia involved reforming and implementing agricultural extension service known as Participatory Demonstration and Training Extension System (PADETES). Therefore, this study investigates the effect of agricultural extension service and other factors on the Technical Efficiency (TE) of teff producers in northern Ethiopia. Using cross sectional data we compare TE level of teff producers who are participants and non-participants of Agricultural Extension (AE) program. We address self-selection in to AE program participation using propensity score matching method. Trans-log stochastic frontier production function is used for TE analysis. The empirical results reveal that, AE program participants’ and non-participants’ farms have an average TE of 72 and 71% respectively. Both groups of farms have considerable overall technical inefficiencies, suggesting the existence of immense potentials for enhancing production through more efficient use of available technology and resources. Determinants of TE are explained significantly by livestock ownership, credit and improved seed. Based on the results, we derive policy recommendations to improve farmers’ teff production performance. These policy measures include the provision of extension services related to technical skill and farm management capacity of the farmers, demand driven livestock extension service, greater access to credit and increasing the availability, quality and adoption of improved seed.